2009
DOI: 10.1007/s10800-009-9833-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on PtRu/C catalyst for methanol electro-oxidation

Abstract: The effect of heat treatment on a commercial PtRu/C catalyst was investigated with a focus on the relationship between electrochemical and surface properties. The heat treated PtRu/C catalysts were prepared by reducing the commercial PtRu/C catalyst at 300, 500, and 600°C under hydrogen flow. The maximum mass activity for the methanol electro-oxidation reaction (MOR) was observed in the catalyst heat treated at 500°C, while specific activity for the MOR increased with increasing heat treatment temperature. Cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…With increase in the CV cycles, the hydrogen desorption peaks increased significantly, which means exposure of Pt on the catalyst surface occurred. A large current density observed at high potential range (0.6-1.2 V) along the positive scan direction significantly decreased with increasing CV cycles, which might come from irreversible oxidation of Ru [43,44] and dissolution of Se [45]. A reduction peak observed between 0.5 and 0.8 V along the negative scan direction decreased with increasing CV cycles, which corresponds to the large decrease of the oxidation/dissolution peak of Ru/Se.…”
Section: Preparation and Characterisation Of Powder Catalystsmentioning
confidence: 90%
“…With increase in the CV cycles, the hydrogen desorption peaks increased significantly, which means exposure of Pt on the catalyst surface occurred. A large current density observed at high potential range (0.6-1.2 V) along the positive scan direction significantly decreased with increasing CV cycles, which might come from irreversible oxidation of Ru [43,44] and dissolution of Se [45]. A reduction peak observed between 0.5 and 0.8 V along the negative scan direction decreased with increasing CV cycles, which corresponds to the large decrease of the oxidation/dissolution peak of Ru/Se.…”
Section: Preparation and Characterisation Of Powder Catalystsmentioning
confidence: 90%
“…PtRu alloy catalysts are widely used as the anode material. 6,7 In the cathode, platinum shows an outstanding performance for oxygen reduction such as the highest catalytic activity and stability. Its high cost, however, is a serious problem.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the surface enrichment of Ir is less severe compared to Pt in Pt−Ru system, as the surface free energy of Ir is analogous to that of Ru (3.231 J m −2 vs 3.409 J m −2 ) at 25°C. 6,34,35 The optimal ratio between Ir and Ru is close to ∼3:1, indicating that an ensemble of three contiguous of Ir atoms might be also necessary for the EOR, during which removal of strongly adsorbed CO might be crucial. Previous in situ differential electrochemical mass spectrometry and Fourier transform infrared spectroscopy studies showed that the selectivity for complete oxidation of ethanol into CO 2 via C−C cleavage is low.…”
mentioning
confidence: 98%
“…Although the surface composition of Ru is unknown in this report, it is expected that surface composition should not differ significantly from bulk composition. This is because the surface enrichment of Ir is less severe compared to Pt in Pt–Ru system, as the surface free energy of Ir is analogous to that of Ru (3.231 J m –2 vs 3.409 J m –2 ) at 25 °C. ,, The optimal ratio between Ir and Ru is close to ∼3:1, indicating that an ensemble of three contiguous of Ir atoms might be also necessary for the EOR, during which removal of strongly adsorbed CO might be crucial.…”
mentioning
confidence: 99%